2016
DOI: 10.1111/tid.12562
|View full text |Cite
|
Sign up to set email alerts
|

Tropheryma whipplei infection (Whipple's disease) in a patient after liver transplantation

Abstract: Whipple's disease (WD) is a rare infection caused by the bacterium Tropheryma whipplei that can affect multiple organs and most commonly occurs in the immunocompetent host. Only 3 cases of WD have been reported in the setting of immunosuppression for organ transplantation. Here, we report the first case of WD, to our knowledge, in a patient after liver transplantation with comorbid graft-versus-host-disease. We discuss the diagnostic challenges in this setting and the value of electron microscopy and in situ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Furthermore, before that episode, the patient received Imipenem as a treatment of urinary tract infections caused by pseudomonas aeruginosa. In the literature, the treatment with antibiotics such as carbapenem antibiotic family, as in the above case may also partially treat or provide prophylaxis against WD [7]. But no enough data are available to prove that a lifelong prophylaxis treatment of WD in renal recipients might be prudent, safe and avoid the relapses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, before that episode, the patient received Imipenem as a treatment of urinary tract infections caused by pseudomonas aeruginosa. In the literature, the treatment with antibiotics such as carbapenem antibiotic family, as in the above case may also partially treat or provide prophylaxis against WD [7]. But no enough data are available to prove that a lifelong prophylaxis treatment of WD in renal recipients might be prudent, safe and avoid the relapses.…”
Section: Discussionmentioning
confidence: 99%
“…All of those cases have occurred in patients having an inflammatory state due to another process affecting the site of Whipple's manifestation. It is possible then that WD risk increases with disruption of innate immunological defenses, such as barrier function and mucosal immunity of the affected tissue by other infections or inflammatory processes [7]. In the liver recipient case, the WD was following liver transplantation with comorbid graft-versus-host disease (GVHD) both affecting the gastrointestinal tract (Table 1) [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, WD can have protean manifestations and can involve any organ of the body including the cardiovascular system with culture-negative endocarditis, or the central nervous system. 4 Mahnel et al, 5 in a comparative study of WD, found that patients who were on immunosuppres-sive medications for possible arthropathies were more likely to develop severe diarrhea leading to the diagnosis of WD. T. whipplei is considered an opportunistic pathogen that persists in duodenal macrophages.…”
Section: Introductionmentioning
confidence: 99%